Establishing a Generalized Repertoire of Initiating Bids for Joint Attention in Children with Autism. Issue 3 (May 2020) - Gomes, Sandra R.; Reeve, Sharon A.; Brothers, Kevin J.; Reeve, Kenneth F.; Sidener, Tina M.
The current study evaluated whether multiple-exemplar training, auditory scripts, and script-fading procedures could establish a generalized repertoire of initiating bids for joint attention in four young children with autism. Stimuli drawn from each of three experimenter-defined categories were used during teaching to program for generalization of initiations of bids for joint attention from trained stimuli to novel stimuli. A fourth category was reserved for assessment of across-category generalization of bids for joint attention. The four categories were (a) visually enticing toys, (b) unusually placed items, (c) environmental sounds, and (d) pictures. Assignment of categories for teaching and assessment of generalization was counterbalanced across the participants. Three different auditory scripts were used during intervention for each of the training stimuli to program for response generalization. All four children learned to initiate bids for joint attention. After scripts were subsequently faded and reinforcement was thinned, bids for joint attention were maintained and also generalized to novel stimuli and settings.